Thermal effects on the instabilities of porous FGM box beams. (1st March 2017) - Ziane, Noureddine; Meftah, Sid Ahmed; Ruta, Giuseppe; Tounsi, Abdelouahed
Highlights: An analytical method to predict the thermal buckling of simply supported and clamped-clamped FGM box beams is presented in this work. A new expression of the critical moment inducing lateral buckling for simply supported beams under thermo-mechanical loads is established. The critical buckling temperature differences obtained by the present method are in excellent agreement with those of Abaqus simulation. Results reveal that if the beams are subjected to high temperature differences, the mechanical load position effect ( ey ) becomes negligible. Abstract: An analytical method to predict the thermal buckling of simply supported and clamped-clamped FGM box beams is presented in this paper. By means of Galerkin's method, a new expression of the critical moment inducing lateral buckling for simply supported beams under thermo-mechanical loads is established. The beam thermo-mechanical properties are graded along the wall thickness according to a power law of the porous volume fraction. The critical temperature gradients given by the present method are compared to those provided by the commercial FEM code Abaqus, and the difference among the results is quite small. To investigate the effects of temperature and porosity on the instabilities of beams, some numerical examples are presented.